Improvement of Nutritional Values of Agaricus Bisporus Mushroom Stalk and Cap through Solid-State Fermentation Using Aspergillus niger - Aydın Altop (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to investigate the effect of solid-state fermentation on the nutritional composition of Agaricus bisporus mushroom stalk and cap. Four homogenous test samples were prepared from the fermented mushroom stalk (Fermented MS), unfermented mushroom stalk (MS), fermented mushroom cap (Fermented MC), and unfermented mushroom cap (MC); each was independently analyzed in triplicates, providing a total of 12 independent measurements of all treatments. Nutritional changes in the mushrooms were determined by analyzing crude protein (CP), ether extract (EE), crude ash (CA), crude fiber (CF), hemicellulose, neutral detergent fiber (NDF), acid detergent lignin (ADL), and acid detergent fiber (ADF) contents. The best improvement in nutritional composition was obtained from the MS with increasing the crude protein (35 %). The results related to other parameters are similar among all the treatments, except for CF. To conclude, the fermented MS can be considered as an alternative protein resource in animal nutrition.